Measurement of Dijet Angular Distributions at s=1.96TeV and Searches for Quark Compositeness and Extra Spatial Dimensions - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (American Physical Society (APS), 2009)
We present the first measurement of dijet angular distributions in pp̄ collisions at s=1.96TeV at the Fermilab Tevatron Collider. The measurement is based on a dataset corresponding to an integrated luminosity of 0.7fb-1 collected with the D0 detector. Dijet angular distributions have been measured over a range of dijet masses, from 0.25 TeV to above 1.1TeV. The data are in good agreement with the predictions of perturbative QCD and are used to constrain new physics models including quark compositeness, large extra dimensions, and TeV-1 scale extra dimensions. For all models considered, we set the most stringent direct limits to date. © 2009 The American Physical Society.